Analisis Harga, Promosi, dan Kualitas Produk Terhadap Keputusan Pembelian Melalui E-Commerce - Develine Micshierly Zenada; Brilliant Brave Adiyono; Aristo Setiawan (STKIP MAJENANG, 2023)
The growth of technology and the internet has significantly boosted the expansion of e-commerce in Indonesia, transforming how people fulfill their needs. As the number of e-commerce users continues to rise each year, marketing strategies in the digital marketplace have evolved. Price is a key factor that greatly impacts marketing strategies. Effective promotions can also motivate consumers to purchase products. Additionally, product quality serves as an added value that enhances a person’s desire to buy. This research aims to analyze the influence of price, promotion, and product quality on consumer decisions to make purchases through e-commerce. To achieve this, the study adopts a qualitative approach by conducting a literature review. The results of this research indicate that price, promotion, and product quality collectively have a positive impact on e-commerce purchasing decisions.